Lies and weddings eaudiobook A novel. - Kwan, Kevin (Books on Tape, 2024)
NEW YORK TIMES BESTSELLER • A TIME MUST-READ BOOK OF THE YEAR • From the iconic internationally bestselling author of the Crazy Rich Asians trilogy: A forbidden affair erupts volcanically amid a decadent tropical wedding in this outrageous comedy of manners. A MOST ANTICIPATED BOOK: The New York Times, The Washington Post, TIME, Entertainment Weekly, Cosmopolitan, CNN, Lit Hub, Minneapolis Star Tribune, Reader's Digest, BookRiot, SheReads, PureWow, Publishers Weekly "Imagine Crazy Rich Asians mated with Saltburn and you've got Lies and Weddings —a heavenly summertime read!"—Plum Sykes, New York Times best-selling author of Bergdorf Blondes   Rufus Leung Gresham, future Earl of Greshambury and son of a former Hong Kong supermodel has a problem: the legendary Gresham Trust has been depleted by decades of profligate spending, and behind all the magazine covers and Instagram stories manors and yachts lies nothing more than a gargantuan mountain of debt. The only solution, put forth by Rufus’s scheming mother, is for Rufus to attend his sister’s wedding at a luxury eco-resort, a veritable who’s-who of sultans, barons, and oligarchs, and seduce a woman with money. Should he marry Solène de Courcy, a French hotel heiress with honey blond tresses and a royal bloodline? Should he pursue Martha Dung, the tattooed venture capital genius who passes out billions like lollipops? Or should he follow his heart, betray his family, squander his legacy, and finally confess his love to the literal girl next door, the humble daughter of a doctor, Eden Tong? When a volcanic eruption burns through the nuptials and a hot mic exposes a secret tryst, the Gresham family plans—and their reputation—go up in flames. Can the once-great dukedom rise from the ashes? Or will a secret tragedy, hidden for two decades, reveal a shocking twist? In a globetrotting tale that takes us from the black sand beaches of Hawaii to the skies of Marrakech, from the glitzy bachelor pads of Los Angeles to the inner sanctums of England’s oldest family estates, Kevin Kwan unfurls a juicy, hilarious, sophisticated and thrillingly plotted story of love, money, murder, sex, and the lies we tell about them all.